Exploring Speaking Anxiety Among Sixth Semester English Education Students at Tadulako University - Nurul Ain; Darmawan Darmawan; Maf'ulah Maf'ulah; Mochtar Marhum (Journal of General Education and Humanities, 2026)
This study examines speech anxiety among sixth-semester English Education students at Tadulako University, highlighting the ongoing challenges that hinder students' ability to communicate confidently despite having taken various speaking courses. This study aims to identify the main factors contributing to speaking anxiety and analyze the coping strategies used by students to overcome these psychological barriers in the classroom context. Using a mixed-methods design that sequentially combined qualitative and quantitative methods, this study first collected quantitative data through a questionnaire administered to sixth-semester students to measure anxiety levels and identify contributing factors, followed by semi-structured interviews with selected participants to gain deeper insights into their personal experiences and management strategies. Findings indicate that speaking anxiety primarily stems from two interrelated domains: psychological factors, including fear of negative evaluation, lack of confidence, and perfectionism; and linguistic factors, such as limited vocabulary, grammatical uncertainty, and pronunciation difficulties. Students reported using various coping mechanisms, ranging from thorough preparation and collaboration with peers to relaxation techniques and talking. This study emphasizes that speaking anxiety is not merely temporary nervousness, but rather a complex phenomenon that affects student participation in class, learning motivation, and their perception of themselves as future English language educators. This highlights the need for a more supportive learning environment and targeted interventions to address the emotional and linguistic dimensions of this challenge.